Effects of a Magnetic Field on the Intergranular Corrosion of Inconel 690 in NaCl Solution - Xu, Dongling; Yuan, Boyu; Li, Liang; Wang, Chao (Frontiers in Materials, 2022)
The intergranular corrosion of Inconel 690 alloy in NaCl solution was investigated using in-line digital holography to observe the dynamic processes occurring at the electrode| electrolyte interface in both the absence and presence of a magnetic field (MF). MF reduced the anodic currents by 6% and 3% at 1.1 V in 0.5 M NaCl (pH=6.44) and 0.5 M NaCl + 0.01 M NaOH (pH=11.5) NaCl solutions respectively because it may increase the amount of Cr on the electrode surface and change the structure of the surface film, thus enhancing the formation of an oxide film; however, MF affected the anodic current little due to the low Lorentz force at the low potential. It was observed that the intergranular corrosion began from a certain grain boundary and developed into other grain boundaries with and without MF. Because the anodic dissolution rate of Fe or Ni is much higher with MF than that without MF and the content of Fe or Ni was higher at a grain boundary than that at the other areas on the surface of the electrode, MF accelerated the intergranular corrosion.